On the role of voice and prosody in argumentation among pre-school children. (21st July 2020) - Bose, Ines; Hannken-Illjes, Kati
Abstract : This paper focuses on the role of voice and prosody in children's argumentation and its relation to framing argumentation as more or less cooperative. Theoretically the project draws from rhetoric, argumentation studies, child studies and linguistics. After a brief overview of the current state in children's argumentation we shall discuss the notion of multimodality in argumentation studies, specifically the role of voice and prosody in argumentation. The paper analyses two instances of child–child argumentation that show striking similarities and differences: Both deal with the same quaestio – that is the same controversial standpoint – and employ similar topoi – that is formal and material resources for arguments. However, they differ with respect to the cooperative framing – that relates in part to the framing of the interaction as fictional or factual – and with respect to the interaction tension. Methodologically, the paper takes a sequential perspective, grounded in conversation analysis and auditory phonetics. We work with longitudinal corpora of authentic child–child communication (3.0–7.0) in play. We argue that other-than-verbal means like voice and prosody play a crucial role in framing the interaction, thereby mediating the degree of cooperativity. This mediation has consequences for the elaboration of argumentative sequences by the children. Thus, voice and prosody we argue, can play a substantial role in argumentation.